2022
DOI: 10.3389/fonc.2022.824235
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplet-Related PLIN2 in CD68+ Tumor-Associated Macrophage of Oral Squamous Cell Carcinoma: Implications for Cancer Prognosis and Immunotherapy

Abstract: BackgroundPLIN2 (adipose differentiation-related protein) belongs to the perilipin family and is a marker of lipid droplets (LDs). Numerous types of tumor exhibit a high PLIN2 level, but its tumorigenic or tumor-suppressive role has been in debate. Recently, LDs serve as innate immune hubs and show antimicrobial capacity. We here aimed to investigate the heterogeneous functions of PLIN2 in the tumor microenvironment and immune regulation.MethodsThis retrospective study included 96 oral squamous cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…49 It exerts tumorigenic or tumor suppressive effects in a tumor-dependent manner. 46 As mentioned above, PLIN2 is associated with a poor prognosis in most cancers. However, other studies, as well as our systematic review and meta-analysis, suggest that inhibition of PLIN2 promotes tumor cell proliferation, tissue entry, and distant metastasis in ccRCC, uterine leiomyoma, 29 and HB.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…49 It exerts tumorigenic or tumor suppressive effects in a tumor-dependent manner. 46 As mentioned above, PLIN2 is associated with a poor prognosis in most cancers. However, other studies, as well as our systematic review and meta-analysis, suggest that inhibition of PLIN2 promotes tumor cell proliferation, tissue entry, and distant metastasis in ccRCC, uterine leiomyoma, 29 and HB.…”
Section: Discussionmentioning
confidence: 92%
“…The included studies used quantitative real-time-polymerase chain reaction or immunohistochemistry to detect the expression level of PLIN2, and all patients were divided into high or low PLIN2 expression groups by cutoff value. In the included studies, there were 10 different malignancies: breast cancer, [34][35][36][37][38] ccRCC, 18,39,40 cutaneous malignant melanoma, 41 HB, 19 hepatocellular carcinoma, 42 highgrade serous ovarian carcinoma, 43 lung adenocarcinomas, 44,45 oral squamous cell carcinoma, 46 pancreatic ductal adenocarcinoma, 47 and salivary duct carcinoma. 48 The result of analysis of survival data from the included studies were obtained following patients for 40-300 months.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
“…8e ). Individual invasion program genes are coherently expressed in macrophages, only increase in non-responders, and include known invasion and metastasis mediators ( CTSL 5 9 , CTSD 60 , CTSB 61 , CHI3L1 62 , SPP1 63 , PLIN2 64 ). Moreover, the invasion program includes cholesterol metabolism genes ( APOE 65,66 , APOC1 67 , CYP27A1 68 , GPNMB 69 ), some which have been linked to the suppression of inflammatory cytokine release (IL-6, TNF-alpha).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, PLIN2 is expressed in other cell types, such as monocytes and macrophages [ 118 ], where its expression was positively correlated with LGALS9 in PDAC; this protein converts polarized macrophages into an M2 phenotype, leading to the inhibited secretion of T-cell cytokines [ 119 ]. These findings suggest that PLIN2 might participate in immunomodulatory effects by regulating tumor-associated macrophages in the tumor microenvironment [ 120 ]. A high-fat diet was able to ameliorate mutated KRAS activity, increasing fibrosis and enhancing PDAC progression in a mouse model [ 121 ], and a recent study with an in vivo mouse model showed a causal and positive correlation between obesity and early PDAC progression, identifying altered beta cell expression of cholecystokinin (Cck) in response to obesity and defining islet Cck as a promoter in oncogenic KRAS-driven PDAC [ 122 ].…”
Section: Metabolic Reprogramming Of the Main Energy Pathways In Pdacmentioning
confidence: 99%